Preparation method of (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy

By preparing (Gd,Mg)2Ni7 type superlattice hydrogen storage alloy, the problem of poor structural stability in the hydrogen absorption process of rare earth alloys is solved, and the high hydrogen absorption/discharge platform pressure and hydrogen storage capacity are achieved, which are suitable for solid-state storage Hydrogen device.

CN116219228BActive Publication Date: 2024-12-17BAOTOU ZHONGKE XUANDA NEW ENERGY TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310198202.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-03
Publication Date
2024-12-17
Estimated Expiration
2043-03-03

AI Technical Summary

Technical Problem

The existing rare earth hydrogen storage alloys are prone to powderization and hydrogen-induced amorphization during the hydrogen absorption process, resulting in poor structural stability and low pressure on the hydrogen absorption/discharging platform, making it difficult to meet the needs of solid hydrogen storage devices and hydrogen refueling stations.

Method used

Using the preparation method of (Gd,Mg)2Ni7 type superlattice hydrogen storage alloy, GdNi, MgNi2 and Ni as precursors, it is prepared according to a specific molar ratio and is carried out in step-by-step sintering method to form an A2B7 type superlattice structure. , the structural stability and hydrogen absorption/discharge performance of the alloy are improved by using the combined action of Gd and Mg elements with small atomic radius.

Benefits of technology

It realizes a hydrogen storage alloy with easy activation, strong cycle stability and high hydrogen absorption/discharging platform pressure. It is suitable for solid hydrogen storage devices and hydrogen refueling stations. The hydrogen storage capacity is greater than 1.60 wt%, and the hydrogen discharge platform pressure is greater than 0.1MPa.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116219228B_ABST
    Figure CN116219228B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy. The alloy uses GdNi, MgNi2 and Ni as precursors, and is prepared by a step-by-step sintering method to obtain a superlattice structure with a crystal structure type of A2B7 type. The preparation method is simple, the process is easy to control, the alloy phase composition and content are effectively controlled, and the hydrogen storage performance of the alloy is guaranteed. The prepared hydrogen storage alloy has the advantages of easy activation, good hydrogen absorption / desorption kinetics, high hydrogen absorption / desorption platform pressure and high hydrogen storage capacity, and is suitable for materials used in equipment or devices such as hydrogen filling stations or hydrogen storage tanks.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of hydrogen storage alloy materials, and in particular to a method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy. Background Art

[0002] Energy crisis and environmental pollution are becoming increasingly serious. Countries around the world have formulated energy security development strategies and set reducing carbon emissions as an important goal. Hydrogen energy, as a renewable energy source, has significant advantages such as abundant reserves, wide sources, high combustion calorific value, clean and pollution-free. The development of the hydrogen energy industry has ushered in new opportunities. The hydrogen energy industry covers a wide range and can be mainly divided into three links: production-storage-transportation-application. Among them, hydrogen energy storage and transportation is a key link, which seriously restricts the terminal application of hydrogen energy. Therefore, achieving safe and efficient storage and transportation of hydrogen is of great significance to promoting the development of the hydrogen energy system.

[0003] The main methods of hydrogen storage include high-pressure gaseous hydrogen storage, low-temperature liquid hydrogen storage, and solid-state hydrogen storage through hydrogen storage materials. Gaseous hydrogen storage has low density and is unsafe, while liquid hydrogen storage requires an insulated hydrogen storage container and has high energy consumption. Solid-state hydrogen storage has the advantages of high hydrogen storage density and high safety, and has received widespread attention. At present, the hydrogen storage materials that have been explored include alloy hydrogen storage materials, complex hydrogen storage materials, porous adsorption hydrogen storage materials, and organic liquid hydrogen storage materials. Among them, rare earth hydrogen storage alloys have good safety and stability, mild hydrogen absorption / desorption conditions, and great application value. Traditional rare earth AB5 alloys are easy to activate and have good hydrogen absorption / desorption kinetics, but the capacity is low; AB2 alloys have high capacity, but this type of alloy is difficult to activate and has a high hydrogen absorption / desorption temperature. Rare earth superlattice alloys show good hydrogen storage performance, good hydrogen absorption / desorption kinetics, good hydrogen absorption / desorption reversibility, and large hydrogen storage capacity. This type of alloy is formed by [A2B4] and [AB5] subunits arranged periodically along the c-axis in a certain ratio and can be divided into AB3 type (1:1), A2B7 type (1:2), A5B 19 Type (1:3) and AB4 type (1:4). The development basis of rare earth superlattice alloys is La-Ni alloys. During the hydrogen absorption process, H occupies the lattice interstitial positions in the [A2B4] and [AB5] subunits and the subunit boundary positions, causing anisotropic expansion and distortion of the lattice. When the stress generated by the lattice expansion during the hydrogen absorption process exceeds the critical stress of the hydride anti-powdering, the stability of the crystal structure is destroyed, causing alloy powdering and amorphous formation, making it difficult to release some hydrogen atoms, increasing the slope of the hydrogen absorption section of the pressure-composition-temperature curve, and attenuating the alloy life. In addition, the La atomic radius is large, the unit cell parameters of the La-Ni alloy superlattice structure are large, and the hydrogen absorption / desorption platform pressure is low, generally below 0.1MPa, which is difficult to meet the application requirements of solid-state hydrogen storage devices and hydrogen refueling stations.

[0004] In view of this, the development of new hydrogen storage alloys that are easy to activate, have fast hydrogen absorption / desorption rates, high hydrogen absorption / desorption platform pressures, and high hydrogen storage capacities is of great significance for improving the performance of hydrogen storage alloys and promoting their practical applications in the field of new energy. Summary of the invention

[0005] The present invention aims to provide a method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy. The alloy uses GdNi, MgNi2 and Ni as precursors, and is prepared by a step-by-step sintering method to obtain a superlattice structure with a crystal structure type of A2B7 type. The preparation method is simple, the process is easy to control, the alloy phase composition and content are effectively controlled, and the hydrogen storage performance of the alloy is guaranteed. The prepared hydrogen storage alloy has the advantages of easy activation, good hydrogen absorption / desorption kinetics, high hydrogen absorption / desorption platform pressure and high hydrogen storage capacity.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] A method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy. The alloy is prepared by a step-by-step sintering method using GdNi, MgNi2 and Ni as precursors in a molar ratio of 1: (0.5-0.7): (1.0-1.40) and pressing into sheets. The alloy has an A2B7 type superlattice structure.

[0008] The ratio of the hydrogen storage alloy precursor provided by the present invention is the key to ensure that the hydrogen storage alloy has good cycle stability, hydrogen absorption / desorption kinetics, and hydrogen absorption / desorption platform pressure. La-Ni based alloys are susceptible to pulverization and hydrogen-induced amorphization, resulting in poor structural stability and reduced cycle life. In addition, because the alloy contains a large number of La atoms, the La atomic radius is large, the alloy unit cell volume is large, and the hydrogen absorption / desorption platform pressure in the pressure-composition-temperature curve is small, it is difficult to meet the requirements of solid-state hydrogen storage devices and hydrogen refueling stations. In AB2 type alloys, when the atomic radius ratio R A / R B The closer it is to 1.225, the more stable the AB2 alloy structure is. In the superlattice alloy system, the 1.225 in the [A2B4] subunit <R Gd / R Ni <R La / R Ni , Gd-Ni alloys have better structural stability and can inhibit structural changes during hydrogen absorption / desorption. In addition, the alloy of the present invention contains a large number of Gd atoms with small atomic radius, the (Gd, Mg)2Ni7 alloy unit cell volume is small, the hydrogen absorption / desorption platform pressure is high, and it is more suitable for solid-state hydrogen storage devices and hydrogenation stations.

[0009] La-Mg-Ni series hydrogen storage alloys are easily affected by pulverization and hydrogen-induced amorphization, have poor crystal structure stability, and have low hydrogen absorption / desorption platform pressure, making it difficult to meet the requirements of solid-state hydrogen storage. The present invention utilizes the interaction between the rare earth element Gd with small atomic radius and strong electronegativity and the Mg atom and the transition metal Ni atom as well as the size effect to prepare a (Gd,Mg)2Ni7 type solid-state hydrogen storage alloy that is easy to activate, has strong cycle stability, has an increased hydrogen absorption / desorption platform pressure, and has enhanced hydrogen absorption / desorption kinetics.

[0010] The hydrogen absorbing element on the A side of the alloy composition of the present invention is the rare earth element Gd. The atomic radius of the Gd element is small, and relative to the La-Mg-Ni alloy R La / R Ni Ratio, R in Gd-Mg-Ni alloy Gd / R Ni The ratio is closer to 1.225, the structural stability is better, and the Gd-Mg-Ni alloy structure unit cell parameters are small, and the alloy hydrogen absorption / desorption platform pressure increases. Mg has an important influence on the structure of hydrogen storage alloys. The participation of Mg helps the alloy to form a stable superlattice structure. The change of Mg content changes the phase structure transformation process. When the Mg content is too low, the alloy is easy to form an AB5 type phase structure. When the Mg content is too high, in addition to entering the superlattice structure, Mg atoms will also form a MgNi2 phase structure, thereby affecting the performance of the hydrogen storage alloy. During the formation process of the alloy described in the present invention, when the Mg element molar ratio is less than 0.5, as the Mg element content decreases, the AB5 type phase structure is easy to exist in the alloy. Although it can increase the alloy hydrogen absorption / desorption platform pressure, it reduces the hydrogen storage capacity of the alloy; and when the Mg element molar ratio is greater than 0.7, as the Mg element content in the alloy increases, the AB2 type phase structure is easy to form in the alloy composition, and the activation performance of the alloy deteriorates. When the molar ratio of the transition metal Ni element on the B side is less than 1.0, as the Ni element content decreases, the chemical composition of the alloy deviates from the A2B7 type phase structure, the prepared alloy will contain a non-superlattice AB2 phase structure and an AB3 type phase structure with poor structural stability, and the alloy cycle stability and activation performance deteriorate. When the molar ratio of the transition metal Ni element on the B side is greater than 1.4, as the transition metal Ni element on the B side increases, the prepared alloy contains AB5 type and A5B 19 The alloy phase structure is complex, the alloy structure stability is poor, it is easily affected by pulverization, and the hydrogen storage capacity of the alloy is reduced.

[0011] As a limitation of the present invention, the preparation method of the (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy is carried out in the following steps:

[0012] (1) Ingredients

[0013] The precursors GdNi and MgNi2 obtained by induction melting are mechanically crushed and ground into powders with a diameter less than 300 mesh, and then mixed with Ni powder to obtain A;

[0014] (2) Tablet pressing

[0015] A was cold pressed under a pressure of 10 MPa to form a blank with a diameter of 1 cm, which was then wrapped with a nickel strip and sealed to obtain B;

[0016] (3) Sintering

[0017] B is placed in a tube furnace and sintered in an argon atmosphere of 0-0.04 MPa to obtain the target alloy.

[0018] As a further limitation of the present invention, the sintering process is carried out in the following order:

[0019] (S1) heating from room temperature to 500°C and keeping at 500°C for 2h;

[0020] (S2) heating from 500°C to 600°C and keeping the temperature for 2h;

[0021] (S3) heating from 600°C to 800°C and keeping the temperature for 2h;

[0022] (S4) raising the temperature from 800°C to 980-1000°C and maintaining the temperature at the target temperature for 110-120h;

[0023] (S5) Cooling to room temperature in the furnace.

[0024] As a further limitation of the present invention, the heating rate of the sintering process is carried out as follows:

[0025] The heating rate of step (S1) is 4°C / min; the heating rate of step (S2) is 2°C / min; the heating rate of step (S3) is 1°C / min; and the heating rate of step (S4) is 1°C / min.

[0026] The (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy prepared by the present invention is used as a material for equipment or devices such as hydrogen refueling stations or hydrogen storage tanks.

[0027] The step-by-step powder sintering process of the present invention is crucial for preparing A2B7 type superlattice (Gd, Mg)2Ni7 type hydrogen storage alloy with uniform structure, which will affect the performance of hydrogen storage alloy. The blank made of precursor is heated to a temperature lower than the melting point of the main component and kept warm, and the material undergoes solid-phase diffusion and peritectic reaction, wherein the main reaction is solid-phase diffusion reaction. The preparation of superlattice hydrogen storage alloy by powder sintering is affected by factors such as sintering temperature, sintering time, and sintering vacuum. Therefore, the reaction conditions must be strictly controlled to improve the efficiency of solid-phase diffusion reaction and increase the uniformity of solid-phase diffusion reaction. In the early stage of sintering, the green body is composed of GdNi powder, MgNi2 powder, Ni powder and the gaps between the above powders. The sintering temperature is raised from room temperature to 500°C, and the original contact points between the precursor powder particles are transformed into crystal bonding, and a sintering neck is formed through atomic processes such as nucleation and crystal growth. When the temperature is further raised to 600°C, the crystal nucleus grows further. When the temperature is further increased by 800℃, atoms migrate to the particle bonding surface in large quantities, the sintering neck is further expanded, the distance between particles is reduced and a continuous pore network is formed, the grains grow, the pores disappear in large quantities, the sintered body shrinks, and the density and strength increase. When the temperature is increased to the target temperature of 980-1000℃, the sintering temperature is relatively high, the density of the sintered body reaches 90%, most of the pores in the green body are completely separated, the number of closed pores increases greatly, and the pore shape tends to be spherical and keeps decreasing.

[0028] The Gd element in the precursor selected for the preparation of the alloy of the present invention has a high melting point, so a higher sintering temperature is selected to reach the solid phase diffusion temperature of the material so that the Gd element can be evenly diffused. When the sintering and holding temperature is lower than 980°C, the solid phase diffusion efficiency of the Gd element in the material is low, resulting in uneven distribution of elements in the alloy, and the formation of an AB2 type non-superlattice phase structure in the obtained alloy, which affects the alloy's hydrogen absorption / desorption kinetics. Due to the low melting point of the Mg element, when the sintering and holding temperature is greater than 1000°C, it is easy to cause the precursor MgNi2 to melt, causing the Mg element to volatilize excessively, and the prepared alloy contains a large amount of AB5 type phase structure, which reduces the hydrogen storage capacity of the alloy. In the sintering process of the present invention, sufficient holding time is required for mass transfer. In the heat treatment process of the present invention, when the holding time of the target temperature is less than 110 hours, the solid phase diffusion is incomplete, some particles are difficult to bond at contact, the alloy structure is unevenly distributed, and it is difficult to obtain the A2B7 type alloy with uniform structure as described in the present invention; and when the holding time is greater than 120 hours, it will cause the product grain eutectoid reaction to form a non-superlattice AB5 type phase structure.

[0029] The alloy preparation method of the present invention provides sufficient reaction conditions for the formation of superlattice (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy. The induction melting method has strict requirements on the reaction temperature. It must reach the melting temperature of the high melting point material before it can be mixed with other metals. Due to the large difference in melting points between the Mg element and rare earth metal elements and transition metal elements, the temperature difference in the furnace changes dramatically at high induction melting temperatures. Low melting point elements such as Mg volatilize in large quantities, which can easily cause alloy element segregation and uneven tissue distribution, seriously affecting the alloy crystal structure and hydrogen storage performance. The present invention prepares the (Gd, Mg)2Ni7 type hydrogen storage alloy through the step-by-step sintering method, which provides mild reaction conditions for the material, can strictly control the volatilization of the Mg element, promote solid-phase diffusion reaction, and is conducive to particle nucleation and crystallization, so as to obtain the target superlattice structure alloy with uniform tissue.

[0030] After adopting the above technical solution of the present invention, the beneficial effects achieved are as follows:

[0031] 1. The (Gd, Mg)2Ni7 type hydrogen storage alloy provided by the present invention has small unit cell parameters, strong structural stability, good cycle stability, high platform pressure, good activation performance and hydrogen absorption / desorption kinetics.

[0032] 2. The preparation method of the (Gd, Mg)2Ni7 type hydrogen storage alloy provided by the present invention is simple, the process is easy to control, the preparation process can well control the phase structure generation, the obtained hydrogen storage alloy has uniform structure, and the hydrogen storage performance of the hydrogen storage alloy is guaranteed.

[0033] 3. The (Gd, Mg)2Ni7 type hydrogen storage alloy provided by the present invention has a reasonable element compatibility. After being prepared by the preparation method of the present invention, the control of the specific phase structure composition is achieved, and finally a hydrogen storage alloy with excellent hydrogen storage performance is obtained. The hydrogen storage capacity of the alloy prepared by the present invention is greater than 1.60wt%, and the hydrogen release platform pressure is greater than 0.1MPa.

[0034] The invention is suitable for preparing a (Gd, Mg)2Ni7 type hydrogen storage alloy, which is further used as a solid hydrogen storage material.

[0035] The technical solution of the present invention will be further described in detail below in conjunction with specific implementation methods and accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] Figure 1 This is the XRD refinement diagram of the hydrogen storage alloy prepared in Example 1 of the present invention;

[0037] Figure 2 This is the XRD refinement diagram of the hydrogen storage alloy prepared in Example 2 of the present invention;

[0038] Figure 3This is the XRD refinement diagram of the hydrogen storage alloy prepared in Example 3 of the present invention;

[0039] Figure 4 The PCT diagram of the hydrogen storage alloy prepared in Example 1 of the present invention;

[0040] Figure 5 The PCT diagram of the hydrogen storage alloy prepared in Example 2 of the present invention;

[0041] Figure 6 The PCT diagram of the hydrogen storage alloy prepared in Example 3 of the present invention;

[0042] Figure 7 The hydrogen absorption curve of the hydrogen storage alloy prepared in Examples 1-3 of the present invention. DETAILED DESCRIPTION

[0043] Unless otherwise specified, the preparation methods described in the following examples all use existing preparation methods, and the raw materials are all commercially available unless otherwise specified.

[0044] Example 1

[0045] This embodiment is a (Gd, Mg)2Ni7 type hydrogen storage alloy, the chemical formula is Gd 0.85 Mg 0.15 Ni 3.50 The preparation process is carried out in the following order:

[0046] (S1) Ingredients

[0047] The precursors GdNi and MgNi2 obtained by induction melting are mechanically crushed and ground into powders with a diameter of less than 300 mesh, and then mixed with Ni powder in a molar ratio of GdNi / MgNi2 / Ni=1:0.5:1.0 to obtain A;

[0048] (S2) Tableting

[0049] A was cold pressed under a pressure of 10 MPa to form a blank with a diameter of 1 cm, which was then wrapped with a nickel strip and sealed to obtain B;

[0050] (3) Step powder sintering

[0051] B was placed in a tubular furnace and sintered in an argon atmosphere of 0-0.04 MPa. The step-by-step powder sintering procedure was as follows: heating from room temperature to 500°C at a heating rate of 4°C / min, and keeping at 500°C for 2 hours; continuing to heating to 600°C at a heating rate of 2°C / min and keeping at this temperature for 2 hours; then heating to 800°C at a heating rate of 1°C / min and keeping at this temperature for 2 hours; then heating to 980°C at a heating rate of 1°C / min and keeping at this target temperature for 110 hours; cooling to room temperature with the furnace to obtain the target hydrogen storage alloy.

[0052] The obtained alloy was mechanically crushed and ground through a 400 mesh sieve. The alloy powder was taken for X-ray diffraction (XRD) test. The results are shown in Figure 1 As shown, from the diffraction peak position and intensity characteristics in the XRD spectrum, it can be seen that the alloy is an A2B7 type hydrogen storage alloy.

[0053] Example 2

[0054] This embodiment is a (Gd, Mg)2Ni7 type hydrogen storage alloy, the chemical formula is Gd 0.80 Mg 0.20 Ni 3.50 The preparation process is carried out in the following order:

[0055] (S1) Ingredients

[0056] The precursors GdNi and MgNi2 obtained by induction melting are mechanically crushed and ground into powders with a diameter of less than 300 mesh, and then mixed with Ni powder in a molar ratio of GdNi / MgNi2 / Ni=1:0.6:1.2 to obtain A;

[0057] (S2) Tableting

[0058] A was cold pressed under a pressure of 10 MPa to form a blank with a diameter of 1 cm, which was then wrapped with a nickel strip and sealed to obtain B;

[0059] (S3) Step powder sintering

[0060] B was placed in a tubular furnace and sintered in an argon atmosphere of 0-0.04 MPa. The step-by-step powder sintering procedure was as follows: heating from room temperature to 500°C at a heating rate of 4°C / min, and keeping at 500°C for 2 hours; continuing to heating to 600°C at a heating rate of 2°C / min and keeping at this temperature for 2 hours; then heating to 800°C at a heating rate of 1°C / min and keeping at this temperature for 2 hours; then heating to 990°C at a heating rate of 1°C / min and keeping at this target temperature for 115 hours; cooling to room temperature with the furnace to obtain the target alloy.

[0061] The alloy was mechanically crushed and ground through a 400-mesh sieve. The alloy powder was taken for XRD testing. The results are shown in Figure 2 As shown, from the diffraction peak position and intensity characteristics in the XRD spectrum, it can be seen that the alloy is an A2B7 type hydrogen storage alloy.

[0062] Example 3

[0063] This embodiment is a (Gd, Mg)2Ni7 type hydrogen storage alloy, the chemical formula is Gd 0.75 Mg 0.25 Ni 3.50 The preparation process is carried out in the following order:

[0064] (1) Ingredients

[0065] The precursors GdNi and MgNi2 obtained by induction melting are mechanically crushed and ground into powders with a diameter of less than 300 mesh, and then mixed with Ni powder in a molar ratio of GdNi / MgNi2 / Ni=1:0.7:1.4 to obtain A;

[0066] (2) Tablet pressing

[0067] A was cold pressed under a pressure of 10 MPa to form a blank with a diameter of 1 cm, which was then wrapped with a nickel strip and sealed to obtain B;

[0068] (3) Step powder sintering

[0069] Place B in a tubular furnace and sinter it in an argon atmosphere of 0-0.04MPa. The step-by-step powder sintering procedure is as follows: heat up from room temperature to 500℃ at a heating rate of 4℃ / min, and keep at 500℃ for 2h; continue to heat up to 600℃ at a heating rate of 2℃ / min and keep at 2h; then heat up to 800℃ at a heating rate of 1℃ / min and keep at 2h; then heat up to 1000℃ at a heating rate of 1℃ / min, and keep at the target temperature for 120h; cool to room temperature with the furnace.

[0070] The alloy was mechanically crushed and ground through a 400-mesh sieve. The alloy powder was taken for XRD testing. The results are shown in Figure 3 As shown, from the diffraction peak position and intensity characteristics in the XRD spectrum, it can be seen that the alloy is an A2B7 type hydrogen storage alloy.

[0071] According to the XRD data after the alloy test obtained in the above Examples 1-3, the XRD tested in Examples 1-3 was refined to obtain the unit cell parameters of the (Gd,Mg)2Ni7 type hydrogen storage alloy crystal structure of Examples 1-3, as shown in Table 1.

[0072] Table 1 Chemical formula, unit cell parameters and phase abundance of alloys in various examples

[0073]

[0074] It can be seen from the table that the alloy phase structures prepared in Examples 1-3 include Ce2Ni7 and Gd2Co7 structures, and as the Mg content increases, the unit cell parameters of the two structures decrease, and the content of the Gd2Co7 phase structure increases.

[0075] Example 4 Performance Test

[0076] The (Gd, Mg)2Ni7 type hydrogen storage alloy prepared in Example 1-3 was removed from the surface oxide layer, mechanically crushed and ground, sieved (300 mesh sieve), and pressed into a sheet with a diameter of 1 cm under a pressure of 10 MPa. The hydrogen storage performance test was carried out to measure the PCT curve and hydrogen absorption / desorption performance of the (Gd, Mg)2Ni7 type alloy at 25°C. The results are as follows: Figure 4-7 shown.

[0077] Depend on Figure 4-6 It can be observed that the maximum hydrogen absorption capacity of the (Gd,Mg)2Ni7 type alloys corresponding to Examples 1-3 at 25°C are 1.64wt%, 1.63wt% and 1.65wt%, respectively, all above 1.6wt%, and the hydrogen release platform pressures are 0.39MPa, 0.45MPa and 0.55MPa, respectively, all above 0.1MPa. The alloy has good activation performance and can reach the maximum hydrogen absorption capacity after the first cycle of hydrogen absorption. It also has good kinetic performance and can reach the maximum hydrogen absorption capacity within 1.5min after activation, as shown in FIG. Figure 7 shown.

[0078] Example 5 Comparative Example

[0079] In order to better illustrate the hydrogen storage performance of a (Gd, Mg)2Ni7 type hydrogen storage alloy provided by the present invention, the present invention compares the performance of some existing hydrogen storage alloys.

[0080] Group A: Hydrogen storage alloy composition is La 0.75 Mg 0.25 Ni 3.50 The alloy is prepared by powder sintering method with LaMgNi4 and LaNi5 as precursors. The alloy structure is Ce2Ni7 type crystal structure. The hydrogen storage capacity of the hydrogen storage alloy at 25°C is 1.56wt.%, and the hydrogen desorption platform pressure is 0.017MPa.

[0081] Group B: Hydrogen storage alloy composition is La 0.60 G 0.20 Mg 0.20 Ni 3.80 The alloy is La 0.6 G 0.2 Mg 0.2 Ni 3.65 and LaMgNi4 as precursors, and are made by powder sintering at 900°C. The alloy phase structure is A5B 19 The alloy has a hydrogen storage capacity of 1.61wt% at 25°C and a hydrogen desorption platform pressure of 0.045MPa.

[0082] Group C: Hydrogen storage alloy composition is La 0.65 Nd 0.15 Mg 0.20 Ni 3.50The metals La, Nd, Mg and Ni are put into an induction melting furnace for melting under an argon atmosphere, and then annealed to obtain an alloy with a crystal structure type of A2B7. The hydrogen storage performance of the alloy is tested. The hydrogen storage capacity of the alloy is 1.57wt% at 25°C, and the hydrogen desorption platform pressure is 0.025MPa.

[0083] Group D: Hydrogen storage alloy composition is Gd 0.72 Mg 0.28 Ni 3.50 The metals Gd, Mg and Ni were put into an induction melting furnace for melting under an argon atmosphere, and then annealed at 1000℃ for 10h to obtain A2B7, AB3, A5B 19 A multiphase alloy with a phase structure was tested for hydrogen storage performance. The hydrogen storage capacity of the alloy was 1.47wt% at 25°C, and the hydrogen desorption platform pressure was 0.34MPa.

[0084] It can be seen from the above-mentioned AD group embodiments that although the alloy of group A has the same structure as the alloy of the present invention and is prepared by a similar method, due to the different alloy elements, the hydrogen storage capacity and hydrogen release platform pressure of the alloy obtained are lower than those of the alloy provided by the present invention; the preparation method of the alloy of group B is similar to that of the present invention, but the alloy is different from the alloy of the present invention, the phase structure of the alloy obtained is different from that of the alloy of the present invention, and the hydrogen release pressure of the alloy is lower than that of the alloy described in the present invention; the crystal structure of the alloy of group C is the same as that of the present invention, but due to the different alloy composition and preparation method, the hydrogen storage performance of the obtained alloy is different from that of the alloy of the present invention, and the hydrogen storage capacity and hydrogen release platform pressure are lower than those of the alloy described in the present invention; the alloy of group D contains the same elements as the alloy of the present invention, but is prepared by a different method, the obtained alloy phase structure is different, and the hydrogen storage capacity of the alloy is lower than that of the alloy described in the present invention.

[0085] It can be seen from the comparative examples that the (Gd, Mg)2Ni7 type hydrogen storage alloy provided by the present invention has better hydrogen storage performance, which is mainly due to the alloy element composition of the present invention, the strictly controlled preparation conditions, and the step-by-step temperature increase powder sintering method. The conditions such as the insulation temperature and the insulation time are closely related to the composition and phase structure formation of the alloy. During the preparation process, the preparation conditions of the present invention can eliminate the internal stress of the alloy, suppress alloy defects, make the grains more complete and uniform, and obtain an alloy with uniform organization and specific structure. The alloy obtained by the present invention has excellent hydrogen storage performance, large hydrogen storage capacity, and high hydrogen release platform pressure, and is suitable for application in hydrogen storage materials of solid-state hydrogen storage devices.

[0086] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy, characterized in that: The alloy is prepared by a step-by-step sintering method using GdNi, MgNi2 and Ni as precursors in a molar ratio of 1:0.7:1.4 and then pressed into sheets. The alloy has an A2B7 type superlattice structure and the chemical formula is Gd 0.75 Mg 0.25 Ni 3.50 , the A2B7 type superlattice structure is a multiphase alloy composed of a Ce2Ni7 phase with a phase abundance of 61.8wt% and a Gd2Co7 phase with a phase abundance of 38.2wt%; The preparation method is carried out in the following steps in sequence: (1) Ingredients The precursors GdNi and MgNi2 obtained by induction melting are mechanically crushed and ground into powders with a diameter less than 300 mesh, and then mixed with Ni powder to obtain A; (2) Tableting A was cold pressed under a pressure of 10 MPa to form a billet with a diameter of 1 cm, which was then wrapped with a nickel strip and sealed to obtain B; (3) Sintering B is placed in a tube furnace and sintered in an argon atmosphere of 0-0.04 MPa to obtain the target alloy; The sintering process is carried out in the following order: (S1) Heating from room temperature to 500°C and keeping at 500°C for 2h; (S2) Heating from 500°C to 600°C and keeping at this temperature for 2h; (S3) Heating from 600°C to 800°C and keeping at this temperature for 2h; (S4) raising the temperature from 800°C to 1000°C and maintaining the temperature at the target temperature for 120 hours; (S5) cooling to room temperature along with the furnace; The heating rate of the sintering process is carried out as follows: The heating rate of step (S1) is 4°C / min; the heating rate of step (S2) is 2°C / min; the heating rate of step (S3) is 1°C / min; and the heating rate of step (S4) is 1°C / min.

2. The method for preparing a (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy according to claim 1, characterized in that: The prepared (Gd, Mg)2Ni7 type superlattice hydrogen storage alloy is used as a material for hydrogen refueling stations or hydrogen storage tanks.

Citation Information

Patent Citations

  • Preparation method and hydrogen storage application of 3R type super stacking single-phase Sm-Mg-Ni alloy

    CN105238956A